2014
DOI: 10.1002/acn3.86
|View full text |Cite
|
Sign up to set email alerts
|

Brain diabetic neurodegeneration segregates with low intrinsic aerobic capacity

Abstract: ObjectivesDiabetes leads to cognitive impairment and is associated with age-related neurodegenerative diseases including Alzheimer's disease (AD). Thus, understanding diabetes-induced alterations in brain function is important for developing early interventions for neurodegeneration. Low-capacity runner (LCR) rats are obese and manifest metabolic risk factors resembling human “impaired glucose tolerance” or metabolic syndrome. We examined hippocampal function in aged LCR rats compared to their high-capacity ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 72 publications
(136 reference statements)
5
35
0
Order By: Relevance
“…The current results supported our hypothesis that patients with comorbid bipolar disorder and MetS associate with the severity of neurodegenerative processes and cognitive impairment than those without [23, 50]. MetS can elicit inflammatory response (increase in the number of reactive astrocytes as well as the levels of interleukin-1-beta and tumor necrosis factor-alpha) and oxidative stress (reactive oxygen species and lipid peroxidation), causing a reduction in the number of neurons in the temporal cortex and hippocampus [23, 51]. Hyperglycemia can directly affect neuron myelin or axons and the structure and function of endoneurial microvessels, which can then induce fiber changes by altering the blood–nerve barrier and inducing hypoxia or ischemia or through unknown mechanisms [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current results supported our hypothesis that patients with comorbid bipolar disorder and MetS associate with the severity of neurodegenerative processes and cognitive impairment than those without [23, 50]. MetS can elicit inflammatory response (increase in the number of reactive astrocytes as well as the levels of interleukin-1-beta and tumor necrosis factor-alpha) and oxidative stress (reactive oxygen species and lipid peroxidation), causing a reduction in the number of neurons in the temporal cortex and hippocampus [23, 51]. Hyperglycemia can directly affect neuron myelin or axons and the structure and function of endoneurial microvessels, which can then induce fiber changes by altering the blood–nerve barrier and inducing hypoxia or ischemia or through unknown mechanisms [52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the leading hypothesis of dopamine receptor hypersensitivity with antipsychotic treatment, a crucial pathophysiological theory of tardive dyskinesia involves neurotoxicity [59]. MetS can elicit inflammatory response and oxidative stress, reducing the number of neurons [23, 51]; animal studies have shown that tardive dyskinesia is associated with inflammation and apoptosis [60, 61]. Furthermore, the potent antioxidants vitamins E and B6 as well as piracetam have been shown to alleviate the severity of tardive dyskinesia in randomized, double-blind, placebo-controlled studies [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…2). Interestingly, inhibitors of Mt bioenergetics produce a pattern of metabolic changes that mimics that observed in brains of AD patients [37•, 61], supporting the critical role of Mt in normal cognitive function. This decline in Mt function is associated with epigenetic silencing of nuclear or Mt DNA and failure of DNA repair that can result in neuronal failure [62].…”
Section: Pathophysiology Of Diabetes and Impaired Cognitionmentioning
confidence: 93%
“…There is evidence of MRI abnormalities including a reduction in hippocampal volumes in both animal models [37•] and human subjects [33, 34, 3840] with IGR. With improvement in glycemic control, there is stabilization of the rate of brain atrophy [33, 34].…”
Section: Mri Diagnosis Of Structural and Functional Changes In The DImentioning
confidence: 99%
See 1 more Smart Citation